Load Effect on Wall Attachment Fluidics Amplifier Performance - AL-Asadi, Ali Abdalmohsin (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
An experimental work has been conducted on wall attachment fluidics amplifiers, one of them to study the effect of output pressure or load on the amplifier performance. The output load has been simulated as a piston connected to the device output and the piston can be loaded accordingly. The results shows that the output volume flow rate increases as the supply pressure increases under different load and the output pressure remains constant as the supply pressure increases under constant load.